“Listen To Us”: Sport for Development Practitioners’ Insights for Funders - Svensson, Per G; Hardie, Ashlyn (Journal of sport for development, 2024)
As sport for development and peace (SDP) initiatives have become more prominent, external stakeholders have adopted unrealistic expectations for program outcomes and funding models. Organizations are often left competing with other grassroots SDP organizations for grants with resource-affluent funders since funding streams have not kept pace with the growth of the field. Although some funders have begun adjusting their approaches, the purpose of this research note was to further explore how practitioners themselves perceive that funders can better support SDP efforts. Open-ended survey responses from grassroots leaders (n=122) highlight a need for long-term funding opportunities, investment in capacity building and overhead expenses, consideration of local contexts, strategic approaches to innovation and entrepreneurial pursuits, and improvement regarding trust and power dynamics.